The effect of amitriptyline treatment on the growth hormone response to apomorphine. - Cowen, P; Braddock, L; Gosden, B (Springer-Verlag, 1984)
The growth hormone response to subcutaneous administration of the dopamine agonist apomorphine (0.005 mg/kg) was assessed in six normal male subjects before and at the end of a course of amitriptyline. Amitriptyline treatment significantly reduced the growth hormone response to apomorphine, confirming the findings of an earlier study in depressed patients. The way in which amitriptyline attenuates the effect of apomorphine is not clear. Direct blockade of dopamine receptors in the hypothalamus is a possibility, but long-term amitriptyline treatment could result in adaptive changes in the monoamine pathways which control GH release.